2014
DOI: 10.1517/14740338.2015.989210
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac risks associated with antibiotics: azithromycin and levofloxacin

Abstract: Introduction Azithromycin and levofloxacin have been shown to be efficacious in treating infections. The adverse drug events associated with azithromycin and levofloxacin were considered rare. However, the US FDA released warnings regarding the possible risk of QT prolongation with azithromycin and levofloxacin. Areas covered Case reports/case series, observational studies and clinical trials assessing cardiovascular risks associated with azithromycin and levofloxacin were critically reviewed, including 15 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 54 publications
1
48
1
6
Order By: Relevance
“…32,33 Similarly, exacerbations are often also treated with antibiotics. Although some antibiotics may increase the risk of cardiac events, 34,35 it is the site of infection more than the choice of antibiotic causing the increased risk. 36 Altogether, the influence of time-dependent confounding caused by these drugs cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Similarly, exacerbations are often also treated with antibiotics. Although some antibiotics may increase the risk of cardiac events, 34,35 it is the site of infection more than the choice of antibiotic causing the increased risk. 36 Altogether, the influence of time-dependent confounding caused by these drugs cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been reported that the long-term, high-dose use of meleumycin can cause dysbacteriosis such as glossitis, angular cheilitis, and pseudomembranous colitis [12]. The other derivatives and metabolites whose structure are similar to the parent drug also have some toxicity and ecotoxicological effects [13][14][15][16][17][18][19][20]. In terms of these six compounds, telithromycin, kirromycin, and meleumycin were new generation of macrolide derivatives, N-demethyl-roxithromycin, Ndemethyl-clarithromycin, and erythromycin A oxime were three metabolites of macrolides.…”
Section: F I G U R Ementioning
confidence: 99%
“…QT interval represents the duration between ventricular depolarization and repolarization on the ECG [35,36]. The prolonged QT interval can be due to congenital heart defects or QT-prolonging drugs, involved in extending the time of the cardiac muscle action potential [37][38][39] Some studies also suggest that increased reactive oxygen species (ROS) production will change the kinetics of hERG potassium conductivity. In a study conducted by Salimi and his colleagues, the isolated heart mitochondria from cardiomyocytes were exposed to erythromycin, azithromycin and clarithromycin.…”
Section: Macrolides Such As Erythromycin and Clarithromycin May Contrmentioning
confidence: 99%